2011
DOI: 10.1097/pcc.0b013e3181e89270
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based mock codes significantly correlate with improved pediatric patient cardiopulmonary arrest survival rates*

Abstract: This study suggests that a simulation-based mock code program may significantly benefit pediatric patient CPA outcomes-applied clinical outcomes-not simply learner perceived value, increased confidence, or simulation-based outcomes. The use of mock codes as an integral part of residency programs could provide residents with the resuscitation training they require to become proficient in their practice. Future programs that incorporate transport scenarios, ambulatory care, and other outpatient settings could fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
205
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(219 citation statements)
references
References 34 publications
5
205
0
9
Order By: Relevance
“…[3][4][5][6][7][8][9][10] However, few multicenter data exist characterizing the impact of simulation training at the patient level, especially in pediatrics. [11][12][13][14][15] Our previous single-center study demonstrated that using simulation to train residents to a minimal standard could improve their clinical success with infant LP. 16,17 However, similar educational programs tested in other environments have not shown any improvements in clinical LP performance.…”
Section: What This Study Addsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] However, few multicenter data exist characterizing the impact of simulation training at the patient level, especially in pediatrics. [11][12][13][14][15] Our previous single-center study demonstrated that using simulation to train residents to a minimal standard could improve their clinical success with infant LP. 16,17 However, similar educational programs tested in other environments have not shown any improvements in clinical LP performance.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Die Implementierung eines Teamtrainingsprogramms führte zu einer verbesserten Krankenhausüberlebensrate nach Reanimation bei Kindern sowie chirurgischen Patienten [935,936]. Die Leistung von Reanimationsteams verbessert sich in realen Reanimationen, aber auch in simulierten ALS-Krankenhausszenarien, wenn spezielle Team-oder Führungstrai-nings in die ALS-Kurse integriert werden [937][938][939][940][941].…”
Section: Training Von Nicht Technischen Fertigkeiten ("Non-technical unclassified
“…The implementation of a simulation-based mock code program has been associated with improved survival from actual cardiopulmonary arrest-with a correlation between survival and the annual incremental increases in the number of mock codes. 20 Quoi de neuf en réanimation pédiatrique? Une mise à jour pratique pour l'anesthésiologiste Le Comité international de liaison sur la réanimation (ILCOR: International Liaison Committee on Resuscitation) compte des membres provenant des principaux groupements de réanimateurs dans le monde, parmi lesquels la Fondation des maladies du coeur du Canada (FMCC) et l'American Heart Association.…”
unclassified
“…La mise en oeuvre d'un programme de faux codes d'alerte pour des simulations a été associé à l'amélioration de la survie dans les cas véritables d'arrêt cardiorespiratoire, avec une corrélation entre le taux de survie et l'augmentation progressive du nombre de faux codes d'alerte au cours de l'année. 20 …”
unclassified